Implications of the Doha market access proposals for developing countries - Laborde Debucquet, David; Martin, Will; van der Mensbrugghe, Dominique (Cambridge University Press, 2012)
This paper uses detailed data on bound and applied tariffs to assess the consequences of the WTO's December 2008 Modalities for tariffs levied and faced by developing countries, and the welfare implications of these reforms. We find that the tiered formula for agriculture would halve tariffs in industrial countries and lower them more modestly in developing countries. In non-agricultural market access (NAMA), the formulas would reduce the tariff peaks facing developing countries and cut average industrial country tariffs by more than a third. We use a political-economy framework to assess the implications of flexibilities for the size of the tariff cuts and find they are likely to substantially reduce the outcome. However, despite the flexibilities, there are likely to be worthwhile gains, with applied tariffs facing developing countries cut by about 20% in agriculture and 28% in NAMA, and sizeable cuts in tariffs facing industrial countries. The welfare impacts of reform are evaluated using a new approach to aggregation that improves on the traditional, flawed approach of weighted-average tariffs. This substantially increases the estimated benefits of an agreement along the lines of these modalities, with estimated global income gains of up to $160 billion per year from market access reform.